Teknik Pendederan Ikan Kerapu Cantik (Epinephelus fuscoguttatus x Epinephelus polyphekadion) dengan Pemberian Probiotik - Yunarty Yunarty; Diana Putri Renitasari (Faculty of Science and Technology University Ibrahimy, 2022)
The beautiful grouper is the result of a cross between the tiger grouper and the batik grouper. Probiotics play a role in increasing enzymes in the digestive tract so that fish grow faster. This research uses the survey method. Data collection techniques, namely primary and secondary. The analysis used regression and quantitative descriptive. The addition of probiotics in feed can increase the growth of fish body weight and length. The survival rate of fish during the rearing period is 65%. The relationship between length and weight has a fairly high correlation. Water quality pH, Do, temperature, and salinity are still in the proper range for fish growth. This means that the addition of probiotics provides a positive increase in growth and water quality.